Characterization of Tumourigenic subpopulations in Nasopharyngeal carcinoma isolated by side population and cancer stem cell marker approaches / Susan Hoe Ling Ling - Susan Hoe, Ling Ling (2017)
Nasopharyngeal carcinoma (NPC) is an epithelial malignancy of the nasopharynx. Studies on NPC tumourigenic subpopulations are often performed in NPC cell lines due to a lack of sizeable NPC tissues. Commonly used methods to identify the subpopulations include sphere-forming culture, side population (SP) assay and cancer stem cell (CSC) markers. The main objective of this study is to characterize the biological properties of tumourigenic cells in NPC isolated separately using SP assay and CSC markers from established NPC cell lines and/or early-passage NPC patient-derived xenografts (PDXs). SP assay identifies stem-like cells by their ability to extrude Hoechst 33342 dye. Using this first approach, SP cells were identified in HK1, a recurrent NPC cell line and in xeno-284, an early-passage NPC PDX established from recurrent metastatic NPC. HK1 contained 5 to 10% of SP cells while xeno-284 had less than 0.5% SP cells. HK1 SP cells significantly formed more holoclones than its non-SP (NSP) cells, an in vitro clone morphology closely related to self-renewal. SP cells also had higher aldehyde dehydrogenase (ALDH) activity than NSP cells, showed asymmetrical cell division and contained slow-proliferating cells. ABCG2, SOX2, TERT, MYC as well as certain Hedgehog, Notch, TGF- and Wnt signalling pathway transcripts were significantly upregulated in SP cells. Despite significant differences seen in vitro and in gene expression experiments, SP and NSP cells showed an overall comparable tumour formation ability and tumour-initiating cell (TIC) frequency in nude mice. CSC markers are successfully used to identify tumourigenic stem-like cells in solid tumours. In the second approach, CD24, CD44, EpCAM and a combination of EpCAM/CD44 markers were used to isolate subpopulations of cells from C666-1, a cell line established from an undifferentiated NPC biopsy and from xeno-B110, an early- passage NPC PDX established from a NPC biopsy. CD44br and EpCAMbr cells from C666-1 and xeno-B110 enriched for faster-growing tumourigenic cells with resulting larger tumours. Marked growth differences in xeno-B110 were associated with higher percentage of S-phase cells and mitotic figures in the marker bright groups as compared to marker dim groups. EpCAM/CD44dbr marker from xeno-B110 did not enhance for faster-growing cells or higher TIC frequency than CD44br marker alone. CD24br, CD44br and EpCAMbr cells from xeno-B110 were more enriched for TICs than their respective dim phenotypes in the first passage and retained self-renewal property upon serial transplantation in vivo for three successive passages. At the final passage of serial transplantation, CD24br cells were 10.55 folds more enriched with TICs than CD24dim cells, CD44br cells had a 7.07-fold enrichment over CD44dim cells and there was a 4.89-fold TIC enrichment for EpCAMbr cells over EpCAMdim cells. KLF4 and CDKN1A transcripts were downregulated in all bright phenotypes which also had induced larger tumour growth, indicating a tumour suppressor role for KLF4 in NPC. Together, the study has shown that SP and CSC markers could isolate NPC cells with differential biological properties in vitro.